Respostas

2014-05-02T12:35:48-03:00
E= 1    +       2
   1-√2        2-√2


    1                   2
 ---------      +   -----------
 1 - 
√2             2 -√2        mmc  de  1-√2 ;  2-√2


1(2-√2) + 2(1-√2)                2 - 1√2 + 2 - 2√2            2 + 2 -  1√2 - 2√2
-----------------------------  =     ------------------------------   =   -------------------------- =
    (1-√2)(2-√2)                  2 - 1√2 - 2√2 +√2√2            2 - 3√2 + √2² 
                                      (aqui fiz a distributiva)


         4 - 3√2                  4 - 3√2
-------------------------  =       -----------  = 1   
      2 - 3√2 + 2               4 - 3√2 



outra maneira
   1                   2
---------      +   ----------
1 - √2             2 -√2 

    1            1          -√2 - 1                   -√2 - 1            -√2 - 1
--------- = ------------- -------------- = ---------------------------- = -------------- = -√2 - 1
1 - √2     -√2 + 1      -√2 - 1          (-√2 + 1)(-√2 - 1)         2 -1


     2              2         -√2 - 2            2 (-√2 -2)            2(-√2 - 2)        2(-√2 -2)
 ---------- = ------------ . -------------- = ------------------------- =-------------------- = ------------ = 
 2 - √2      -√2 + 2     -√2 - 2        (-√2 + 2)(-√2 - 2)        2  -  4                -2
         
-1(-√2 - 2) = √2 + 2
 
 
 -√2 - 1 + √2 + 2  = -1 +2 = 1           



Resposta = 1